Determination and risk assessment of naturally occurring genotoxic and carcinogenic alkenylbenzenes in basil-containing sauce of pesto. (2017) - Al-Malahmeh, Amer J.; Al-ajlouni, Abdalmajeed M.; Wesseling, Sebastiaan; Vervoort, Jacques; Rietjens, Ivonne M.C.M.
Abstract: A risk assessment of basil-based pesto sauces containing methyleugenol and related alkenylbenzenes was performed based on their levels detected in a series of pesto sauces available on the Dutch market. The estimated daily intake (EDI) values of alkenylbenzenes as a result of consumption of the different pesto sauces amounted to 1.2–44.3 μg/kg bw for individual alkenylbenzenes, 14.3–43.5 μg/kg bw when adding up the alkenylbenzene levels assuming equal potency, and 17.3–62.9 μg/kg bw when expressed in methyleugenol equivalents using alkenylbenzenes defined toxic equivalency factors (TEF). The margin of exposure approach (MOE), used to evaluate the potential risks, resulted in MOE values that were generally lower than 10000 indicating a priority for risk management when assuming daily consumption. The levels of methyleugenol detected in the pesto sauces would allow consumption of 1.1–29.8, 7.5–208, 15.1–416.5, and 32.4–892.5 g of pesto sauce on a daily basis, once a week, once every two weeks, and once a month, respectively, to achieve MOE values above the 10000 limit indicating low priority for risk management. It is concluded that consumption of pesto sauces would only be of concern if consumed on a daily basis over longer periods of time.